THE EFFECT OF RED GUAVA-RED SPINACH JUICE COMBINED WITH IRON SUPPLEMENTATION ON HEMOGLOBIN LEVELS IN PREGNANT WOMEN - Sukati Sarmin; Restu Pangestuti; Fifi Ratna Aminati (Nurse and Holistic Care, 2025)
Background: Anemia in pregnancy remains a major public health concern, with prevalence exceeding 20% in Indonesia. This condition is commonly associated with hemodilution and inadequate iron intake. Objective: This study aims to analyze the effect of red guava–red spinach juice combined with iron (Fe) tablet fortification on the hemoglobin (Hb) levels of third‑trimester pregnant women. Methods: A quasi‑experimental pretest–posttest design with a control group was implemented involving 60 pregnant women. Participants were divided into control (Fe tablets only) and intervention groups (Fe tablets + 200 mL red guava–red spinach juice daily for 14 days). Hemoglobin was measured using a calibrated digital hemoglobinometer. Paired and independent t‑tests were used. Result: The control group showed an Hb increase from 9.21 ± 0.18 g/dL to 12.10 ± 0.27 g/dL (mean difference 2.89 g/dL, p < 0.001). The intervention group increased from 8.41 ± 1.12 g/dL to 13.00 ± 0.90 g/dL (mean difference 4.59 g/dL, p < 0.001). An independent t‑test revealed significant differences in post‑test Hb levels between groups (t = −20.4, p = 0.01). Effect size (Cohen’s d = 1.21) indicated strong clinical significance. Conclusion: Red guava–red spinach juice combined with Fe tablets is more effective in increasing Hb levels than Fe tablets alone. This intervention can be recommended as a complementary non‑pharmacological strategy for anemia prevention programs.